Antiaromaticity to Aromaticity: From Boroles to 1, 2‐Azaborinines by Ring Expansion with Azides. Issue 32 (25th June 2014) - Braunschweig, Holger; Hörl, Christian; Mailänder, Lisa; Radacki, Krzysztof; Wahler, Johannes
Abstract We have exploited the reactivity of antiaromatic boroles, gaining access to aryl‐substituted monocyclic 1, 2‐azaborinines. The observed ring‐expansion reaction of inherently electron‐deficient boroles with organometallic and organic azides is demonstrated for representative examples. This substance class is expected to provide a new avenue into 1, 2‐azaborinine chemistry, especially in the area of functional organoboron materials. Our results are based on NMR and UV/Vis spectroscopy as well as single‐crystal X‐ray crystallography and provide a virtually quantitative approach that also offers numerous points of variation.